Mrs. jeffries sweeps the chimney eaudiobook - Brightwell, Emily (Mrs. Jeffries, 2019)
She keeps house for Inspector Witherspoon . . . and keeps him on his toes. Everyone's awed by his Scotland Yard successes—but they don't know about his secret weapon. No matter how messy the murder or how dirty the deed, Mrs. Jeffries's polished detection skills are up to the task . . . proving that behind every great man there's a woman—and that a crimesolver's work is never done. Inspector Witherspoon is perplexed. No one seems to know the identity of the dead man dressed like a vicar and propped up against the outside wall of St. Paul's Church. A paper clutched in the corpse's hand reveals the address of a dilapidated and seemingly abandoned cottage—abandoned if you don't count the human skeleton stuffed in the chimney. To link these two bizarre incidents will take all of the resources at Witherspoon's command—and a little help from the efficient Mrs. Jeffries . . .